Tenochtitlan: Reflection on myth in the construction of Modernity in Latin America - Hernández Castro, Gustavo (2020)
This article aims to explain the relationship between the mythical successionin the fall of the city of Tenochtitlan at the hands of the Spanish conquerors,from the Vision of the Vanquished (León-Portilla, 1992), CrónicaMexicayotl (Alvarado Tezozomoc, 1992) and the Imaginary happening fromthe novel TENOCHTITLAN. The last battle of the Aztecs (Sánchez, 2009).The narrations are contrasted, to understand that from a mythical vision ofhistorical events (first and second modernity), subjectivities, realities andsustained experiences are built (historical witnesses) that support the explanationsof the fall of an empire, the crumbling of a complete civilization atthe hands of foreign conquerors, and consequently the prolongation of a geoculturalimaginary of the world-system, which characterizes the modernityof Latin America.